THE ROLE OF AUDIT IN CORPORATE GOVERNANCE - ERMATOV AKMALJON AKBARALIEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article reveals the essence of internal audit as a structural unit of the enterprise, and also describes the role of the audit and internal audit services in enterprise risk management during the transition to the digital economy. Achievement of goals by the organization in carrying out activities largely depends on effective risk management. This article discusses a detailed analysis of risks and stages of elimination of risks existing at the enterprise by the audit service. It describes the typical mistakes made by the audit services in business entities, as well as recommendations for their elimination, the possibility of improving the ability to predict the organization’s activities based on risk management.